Managers’ ability to cope with stress in the work settings - Župerkienė, Erika (Business, Management and Economics Engineering, 2010)
The article analyses the type of expression of manager professional stress. The main features of professional stress are discussed taking into consideration the problems, which can arise due to stress at work. Impact of long-lasting stress suffered at work is displayed through the changes in managers‘ behaviour, which reduces management effectiveness, causes health problems and pathological changes in the organism systems. By means of a standardized test, stress management skills of managers of Lithuanian small and medium-size business companies are disclosed: elimination of stress factors, resistance to stress, temporary means of coping with stress. The most relevant reasons, which cause managers’ stress at work, are identified. The results of survey show that managers’ ability to cope with stress in the work settings is insufficient: the best developed stress management skill amongst the respondents is ability to eliminate stress factors; while resistance to stress is poorly developed, the skill in applying temporary means of relaxation is also subject to improving. In order to develop stress management skills, managers are recommended to use a strategy for elimination of stress factors: to plan time, strengthen resistance to stress by developing emotional intellect, by creating cooperating teams of employees, delegating authority, developing competencies of communication and work reorganization. For individual development of resistance to stress it is recommended to maintain healthy lifestyle and apply temporary means of relaxation when the need arises. Article in Lithuanian. Vadovų gebėjimas valdyti darbe kylantį stresą